Biotechnology Applications of Plant Callus Cultures. (February 2019) - Efferth, Thomas
Abstract: In ethnopharmacology, and especially in traditional Chinese medicine, medicinal plants have been used for thousands of years. Similarly, agricultural plants have been used throughout the history of mankind. The recent development of the genetic engineering of plants to produce plants with desirable features adds a new and growing dimension to humanity's usage of plants. The biotechnology of plants has come of age and a plethora of bioengineering applications in this context have been delineated during the past few decades. Callus cultures and suspension cell cultures offer a wide range of usages in pharmacology and pharmacy (including Chinese medicine), as well as in agriculture and horticulture. This review provides a timely overview of the advancements that have been made with callus cultures in these scientific fields. Genetically modified callus cultures by gene technological techniques can be used for the synthesis of bioactive secondary metabolites and for the generation of plants with improved resistance against salt, draft, diseases, and pests. Although the full potential of callus plant culture technology has not yet been exploited, the time has come to develop and market more callus culture-based products.